Принцип численно-полевого анализа гармонического состава ЭДС в турбогенераторе - Милых, Владимир Иванович; Полякова, Наталия Владимировна (Изд-во ООО "Наука и Технологии", 2012)
На основе численных расчетов вращающихся магнитных полей турбогенератора и использования мгновенных значений магнитного потокосцепления определены временные функции ЭДС его трехфазной обмотки и проведен гармонический анализ этих ЭДС в различных расчетных режимах.

Numerical computations of rotating magnetic fields of a turbogenerator are applied to evaluating time functions of the turbogenerator three-phase winding EMF using instantaneous magnetic linkage values, harmonic analysis of these EMF accomplished in various rated conditions.
Principle of the numeral-field analysis of harmonic analysis composition EMF in a turbogenerator
Keywords: турбогенераторы; магнитное поле; численные расчеты; магнитное потокосцепление; ЭДС; гармонический анализ; turbogenerator; magnetic field; numeral calculations; magnetic linkage; EMF; harmonic analysis